Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/bcr-2018-225592
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-associated haemophagocytic lymphohistiocytosis: a rare cause of febrile neutropenia during cancer chemotherapy

Abstract: Febrile neutropenia (FN) is a common complication in patients with cancer during treatment with antineoplastic drugs. The initial cause is usually bacterial, and treatment of FN follows well-defined algorithms. We report a case of a 62-year-old patient with chronic lymphocytic leukaemia (CLL), who developed FN, which was unresponsive to both empirical antibacterial and empirical antifungal therapy. Surprisingly, a diagnosis of the life-threatening condition haemophagocytic lymphohistiocytosis (HLH) associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Likewise, development of HLH in the post-HSCT setting is rare and requires caution during diagnosis and management, as many conditions may mimic or trigger HLH. 20,21 In the current report, 2 children developed HLH post-HSCT, which was triggered by CMV in 1 patient and adenovirus in the other. Both patients have significant hemophagocytosis in the bone marrow.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Likewise, development of HLH in the post-HSCT setting is rare and requires caution during diagnosis and management, as many conditions may mimic or trigger HLH. 20,21 In the current report, 2 children developed HLH post-HSCT, which was triggered by CMV in 1 patient and adenovirus in the other. Both patients have significant hemophagocytosis in the bone marrow.…”
Section: Discussionsupporting
confidence: 45%
“…14,15 When it develops during treatment for ALL, it imposes a diagnostic and therapeutic challenge, and it is not restricted to intensive treatment phases but also can be equally fatal during maintenance therapy. [14][15][16][17][18][19] Lehmberg et al reported that infectious triggers were identified in 29% of malignancy-associated HLH and 88% of chemotherapy-related HLH. Infectious triggers in this population included EBV, herpes simplex virus, VZV, CMV, Escherichia coli septicemia and aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…CMV is a member of the herpesvirus family and is known to cause a wide range of infection symptoms. While in immunocompetent individuals, primary CMV infection could be mild and self-limited, CMV infection or reactivation of a dormant infection could be a devastating complication for immunocompromised patients with autoimmune disease, organ transplant recipients, and/or those receiving immunosuppressive therapy 16 17. CMV can also cause secondary HLH and manifest similarly to MAS caused by rheumatological diseases 18.…”
Section: Discussionmentioning
confidence: 99%
“…Positive viral serologies with IgG and IgM and positive CMV-DNA PCR (generally greater than 10 000 copies/mL) indicating active infection are usually seen 20–22. In CMV-induced HLH, most patients receive both antiviral and immunosuppressive therapies (usually high-dose steroids such as dexamethasone), with or without the chemotherapy etoposide, with an expected response in usually 3–10 days 17 19 23. Ganciclovir (or its prodrug valganciclovir) is usually the first-line antiviral medication, while foscarnet is considered the second-line treatment if there is a concern for bone marrow suppression from the former agents 24.…”
Section: Discussionmentioning
confidence: 99%
“…Pasvolsky et al recently described a case series highlighting the diagnostic challenge of M-HLH as the presenting manifestation of lymphoma, with two of the four patients dying before a diagnosis of lymphoma was made despite HLH-directed therapy. 18 HLH associated with CLL has been described with disease transformation, 19,20 (seeTable 2) infections [21][22][23][24][25][26] , or ibrutinib treatment 27 (Table 2). Ours is the fourth case reported in which no trigger was identified 28,29,32 (see Table 2).…”
Section: Discussionmentioning
confidence: 99%